A Review on Design Analysis and Optimization of Front Axle For Commercial Vehicle - Tarun Kumar Yadav; Anshul Gangele (AG Volumes, 2021)
To remain competitive in today's market, it is critical for manufacturers to provide new products to consumers at a lower cost and quicker than their competitors. The Front axle beam accounts for up to 40% of the vehicle's load-carrying capability. The existing measuring system shows quite a poor acceptability for the proposed design of the cross pin, except for the micrometer. A review is presented here on design analysis and optimization of cross pin. Literature is also studied of researchers and presented here on the same topic.